Bawei Chenxiang Wan Ameliorates Cardiac Hypertrophy by Activating AMPK/PPAR-α Signaling Pathway Improving Energy Metabolism - Zhang, Xiaoying; Zhang, Zhiying; Wang, Pengxiang; Han, Yiwei; Liu, Lijun; Li, Jie; Chen, Yichun; Liu, Duxia; Wang, Jinying; Tian, Xiaoying; Zhao, Qin; Yan, Fengxia (Frontiers in Pharmacology, 2021)
Bawei Chenxiang Wan (BCW), a well-known traditional Chinese Tibetan medicine formula, is effective for the treatment of acute and chronic cardiovascular diseases. In the present study, we investigated the effect of BCW in cardiac hypertrophy and underlying mechanisms. The dose of 0.2, 0.4, and 0.8 g/kg BCW treated cardiac hypertrophy in SD rat model induced by isoprenaline (ISO). Our results showed that BCW (0.4 g/kg) could repress cardiac hypertrophy, indicated by macro morphology, heart weight to body weight ratio (HW/BW), left ventricle heart weight to body weight ratio (LVW/BW), hypertrophy markers, heart function, pathological structure, cross-sectional area (CSA) of myocardial cells, and the myocardial enzymes. Furthermore, we declared the mechanism of BCW anti-hypertrophy effect was associated with activating adenosine 5'-monophosphate (AMP)-activated protein kinase (AMPK)/peroxisome proliferator–activated receptor-α (PPAR-α) signals, which regulate carnitine palmitoyltransferase1β (CPT-1β) and glucose transport-4 (GLUT-4) to ameliorate glycolipid metabolism. Moreover, BCW also elevated mitochondrial DNA-encoded genes of NADH dehydrogenase subunit 1(ND1), cytochrome b (Cytb), and mitochondrially encoded cytochrome coxidase I (mt-co1) expression, which was associated with mitochondria function and oxidative phosphorylation. Subsequently, knocking down AMPK by siRNA significantly can reverse the anti-hypertrophy effect of BCW indicated by hypertrophy markers and cell surface of cardiomyocytes. In conclusion, BCW prevents ISO-induced cardiomyocyte hypertrophy by activating AMPK/PPAR-α to alleviate the disturbance in energy metabolism. Therefore, BCW can be used as an alternative drug for the treatment of cardiac hypertrophy.